PENGEMBANGAN MODUL PRAKTIKUM BERBASIS PROBLEM BASED LEARNING PADA ALAT PERAGA CONTINOUSLY VARIABLE TRANSMISSION (CVT) SEPEDA MOTOR - Yusrin Kadir; Muhammad Yasser Arafat; Hendra Uloli (Universitas Negeri Gorontalo, 2022)
Motorcycle Technology is a theoretical and practical course in the UNG Mechanical Engineering Education S1 Study Program in the automotive concentration. Based on the results of observations that have been made by researchers that in the laboratory there are Continously Variable Transmission (CVT) motorcycle props but do not yet have a module or guide so that how to use these props is still not understood, the authors took the initiative to develop a practicum module as an alternative to overcome this problem by using the Problem Based Learning learning model on the learning media of the motorcycle Continously Variable Transmission (CVT) teaching aid. The objectives of this development research are 1) Developer of the problem based learning practicum module on the Continously Variable Transmission (CVT) motorcycle prop using the RD (Research and Development) method and using the 4D model. 2) Knowing the feasibility of the Continously Variable Transmission (CVT) motorized vehicle module developed. The method used in this study is the RD (Research and Development) method and uses a 4D model (four-D model). The results of the development of a motorcycle Continously Variable Transmission (CVT) practicum module made using the 4D model research and development (RD) method consisting of the Define, Design, Develop, and Disseminate stages. Based on the results of design validation that has been done with a percentage of 96%. The results were validated by material experts with 94% results. The results of the validation by media experts with the results of 85%. The results of the student response test instrument with a result of 81%. This shows that the motorcycle Continously Variable Transmissin (CVT) practicum module can be declared